Description of four new species of the Neotropical Micropotamia Carvalho (Diptera, Muscidae) - Jorge, Stela Costa; Carvalho, Claudio José Barros De (Zootaxa, 2024)
Micropotamia Carvalho (Diptera, Muscidae) is a Neotropical genus with four species distributed from Mexico to southern Brazil. Here, we describe four new species in the genus: Micropotamia stellaria sp. nov. from Cruzeiro do Sul, Acre, Brazil, Micropotamia ananas sp. nov. from Borba, Amazonas, Brazil, Micropotamia ditissima sp. nov. from Rio Nhamundá, Amazonas, Brazil, and Micropotamia fortuna sp. nov. from Est. La Casona, Prov. Puntarenas, Costa Rica. An identification key for all species is provided.